Traffic driven multiple constraint-optimisation for QoS routing. (4th August 2005) - Goodridge, Wayne S.; Robertson, William; Phillips, William J.; Sivakumar, Shyamala
The core of any QoS routing algorithm designed to solve the multi-constrained optimal path problem, is a length function that is used to find the optimal route across the network. User applications require diverse optimisation requirements but typical QoS-based algorithms have fixed length functions and do not offer a flexible optimisation framework. In this paper, we present a multiple-constraint-optimisation algorithm that adapts to user traffic optimisation needs without requiring a change to core logic or the length function. This routing paradigm searches for feasible paths satisfying multiple QoS requirements and implements a routing decision support system (RDSS) that separates the constraint path finding mechanism from the optimisation mechanism. Thereby the algorithm can optimise for any type or combination of metrics. Simulations compare the performance of the RDSS algorithm with other QoS algorithms and demonstrate the feasibility of the proposed approach in finding pareto optimal paths especially under strict constraints.